Le rôle de l’intox dans la construction de l’ethos de Marine Le Pen pendant la campagne présidentielle en France 2017 - Pachocińska, Elżbieta (Studia Romanica Posnaniensia, 2017)
This study examines the nature and function of manipulative discourses by Marine Le Pen’s, the candidate of Front National in the 2017 French presidential elections. It also shows how manipulative discourse legitimates her populist ethos. We adopt the discursive and rhetorical perspective (Charaudeau, 2011, 2015 ; Taguieff, 1984), which is illustrated by a corpus of texts by fact-checking journalists (les Décodeurs, Désintox) of Le Monde and Libération newspapers, as well as a video of a presidential debate.